A 10-Year Review of Designated Leadership Positions of the American Orthopaedic Foot & Ankle Society (AOFAS). Issue 4 (October 2022) - Chrea, Bopha; Johnson, Holly; Baumhauer, Judith; Holleran, Amanda; Atwater, Lara C.; Poon, Selina
Background: In 2019 the majority of US medical students were women (50.5%). However, despite this representation, female representation within orthopaedic surgery remains low when compared to male counterparts. Previously, the American Society for Surgery of the Hand (ASSH) and Pediatric Orthopaedic Society of North America (POSNA) published their gender diversity data. No such study has been conducted in the American Orthopaedic Foot & Ankle Society (AOFAS), which is the largest membership organization for foot and ankle–trained orthopaedic surgeons. This study sought to investigate whether increased female representation in the AOFAS membership roster is reflected in different levels within the organization. Methods: The 2012-2022 membership rosters were obtained from the AOFAS and compared by gender. Volunteer, elected, and appointed leadership positions as well as rates of engagement were compared for each of the activities. Leadership positions were defined as committee chair, vice chair, or board of directors (BOD). When available, time for advancement through leadership positions to the presidential role was analyzed by gender. Comparative data were available for 2 other respective subspecialty groups, ASSH and POSNA, from previously published studies. Results: Between 2012 and 2022, the percentage of female membership in the AOFAS has continued to increase from 7.5% (n=76) to 13% (n=163). Engagement in committee membership positions during this time has more than doubled from 11 of 26 (14.4%) to 57 of 163 (34.9%). When participation trends were evaluated by gender, women showed higher rates of committee involvement than their male counterparts. In 2021 compared to 2012, the percentage of female committee members more than doubled compared with their male counterparts (female 34.9% to male 23.2% vs female 14.4% to male 16.8%). This increase in female gender committee composition trend has been seen in the ASSH and POSNA, but it is more pronounced in the AOFAS. Representation of women in committee chair positions and elected positions has not seen this same parallel increase. Conclusion: The female membership of the AOFAS has a similar gender composition to other orthopaedic subspecialities. Female membership within the society has increased over the past 10 years. The rates of female involvement within committee membership positions have seen a parallel increase. It will take time to mature into leadership roles as we continue to increase diversity within our respective subspecialty organizations. Inception of the AOFAS Diversity Equity and Inclusion and Women's Subcommittee demonstrate a continued emphasis on this core value within the society. Level of Evidence: Level IV, cohort study.